Does quality disclosure improve quality? Responses to the introduction of nursing home report cards in Germany - Annika Herr; Thu-Van Nguyen; Hendrik Schmitz (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
Since 2009, German nursing homes have been evaluated regularly with quality report cards published online. We argue that most of the information in the report cards does not reliably measure quality of care, but a subset of seven measures does. Using a sample of more than 3,000 nursing homes with information on two waves, we find a significant improvement in the nursing home quality from the first to the second evaluation. Both indicators comprising either the two outcome quality measures or the seven measures indicating "risk factors" in the report cards improve. This can be interpreted as evidence that quality disclosure positively affects the (reported) quality in nursing homes.
Keywords: L15; I11; I18; 330; public reporting; quality; long-term care; information